Topical ionic contra‐viral therapy comprised of digoxin and furosemide as a potential novel treatment approach for common warts - Kolk, T.; Dillingh, M.R.; Rijneveld, R.; Klaassen, E.S.; Koning, M.N.C.; Kouwenhoven, S.T.P.; Genders, R.E.; Bouwes Bavinck, J. N.; Feiss, G.; Rissmann, R.; Burggraaf, J. (Journal of the European Academy of Dermatology and Venereology, 2017)
Background DNA viruses such as HPV rely on K+ influx for replication. Both digoxin and furosemide inhibit the K+ influx by interacting with cell membrane ion co‐transporters (Na+/K+‐ATPase and Na+‐K+‐2Cl− co‐transporter‐1, respectively). We therefore hypothesized that these two compounds in a topical formulation may be valuable in the treatment of HPV‐induced warts. This new approach is called Ionic Contra‐Viral Therapy (ICVT). Objective To evaluate systemic exposure, safety and tolerability of ICVT with a combination of furosemide and digoxin after repeated topical application in subjects with common warts. Furthermore, we aimed to evaluate pharmacodynamics effects of ICVT. Methods Twelve healthy subjects with at least four common warts on their hands were included in the study and treated with a fixed dose of 980 mg topical gel containing 0.125% (w/w) digoxin and 0.125% (w/w) furosemide for 7 consecutive days on their lower back to assess safety and systemic exposure. Two warts were treated with 10 mg each and two served as negative controls to obtain preliminary evidence of treatment effect. Results ICVT was well tolerated topically, and there was no evidence of systemic exposure of digoxin or furosemide. There were no clinical relevant safety findings and no serious adverse events (SAEs). A rapid and statistically significant reduction in diameter, height and volume of the warts was already observed at day 14. Conclusion ICVT was found to be safe for administration to humans and 7 days of active treatment showed a statistical significant wart reduction compared to untreated control lesions, clearly indicating pharmacological activity.